Fine molecular structure and its effects on physicochemical properties of starches in potatoes grown in two locations. (December 2019) - Ahmed, Sulaiman; Ru, Weidong; Han, Huaxin; Cheng, Linrun; Bian, Xiaobo; Li, Guangcun; Jin, Liping; Wu, Peng; Bao, Jinsong
Abstract: Seven potato cultivars were planted at two different locations, E1 (Yiwu) and E2 (Jinhua) to assess the starch molecular structures and physicochemical properties as affected by growing locations. Most of the potato cultivars in E2 presented significantly smaller average whole molecular size ( R h ¯ ) whereas larger average chain length of amylopectin ( X ¯ ) along with lower proportion of fa chains (DP 6–12) than those in E1. Significant varietal difference in the physicochemical properties were observed within each location, but only the mean onset temperature in E1 was significantly lower than that in E2. The fine structures (chain-length distribution) of both amylose and amylopectin affected the pasting properties of potato starches based on the starch structure-property correlations. The amylopectin fine structure also determined the thermal and retrogradation properties. Potato starches with more short chains and less long chains of amylopectin displayed lower gelatinization temperature but higher retrogradation. Graphical abstract: Image 1 Highlights: Molecular size and chain-length distributions varied among seven potato genotypes and between two locations. The pasting viscosities are determined by both amylose and amylopectin fine structures. More short chains or less long chains of amylopectin decreased gelatinization temperature (To and Tp). Retrogradation enthalpy and percentage increased with more short chains or less long chains of amylopectin.